2022
DOI: 10.1186/s12917-022-03376-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of different sedative doses of dexmedetomidine on the intestinal motility in clinically healthy donkeys (Equus asinus)

Abstract: Aim Gastrointestinal effects of different doses of dexmedetomidine in donkeys are still unidentified. The current study aimed to evaluate the impact of different doses of dexmedetomidine on the motility of selected parts of the gastrointestinal tracts in donkeys using transabdominal ultrasonography. Materials and methods An experimental crossover study was conducted on 30 healthy donkeys of both sexes (15 males and 15 females; 160 ± 60 kg). With a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…This study found increased in vitro contractility of the LSM with dexmedetomidine treatment, which conflicts with two in vivo studies that found decreased gut sounds following dexmedetomidine administration in horses [ 18 , 21 ]. This illustrates the fact that in vitro contractile activity does not necessarily translate to an increased motility in vivo.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study found increased in vitro contractility of the LSM with dexmedetomidine treatment, which conflicts with two in vivo studies that found decreased gut sounds following dexmedetomidine administration in horses [ 18 , 21 ]. This illustrates the fact that in vitro contractile activity does not necessarily translate to an increased motility in vivo.…”
Section: Discussioncontrasting
confidence: 99%
“…Medetomidine and its active D-isomer dexmedetomidine are more selective α2 agonists that are not as commonly used in horses, yet are known produce effective and safe sedation [ 18 , 19 , 20 ]. These drugs have also been shown to affect intestinal function, with medetomidine decreasing intestinal circular smooth muscle contractility in vitro [ 16 ], and decreased borborygmia being documented the first hour after dexmedetomidine administration in horses and donkeys [ 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there been studies in adult patients that have shown that DEX does impact upper esophageal sphincter function with pharyngeal swallowing and depressed the contractile function of the proximal esphagus with esophageal swallowing [25]. In animal studies, DEX has shown to have a dose-dependent effect on the inhibition of gastrointestinal motility (duodenum, jejunum, colon and cecum) in donkeys [26]. However, the effects on the lower gastrointestinal tract in humans suggest that DEX may have a positive effect on improving return of motility following abdominal surgery in adult patients [27].…”
Section: Discussionmentioning
confidence: 99%